The Impact of the Narrative on the Experience of the Disease - Méndez del Portal, Rocío (2021)
This article seeks to reflect on the impact of the narrative on the experience of illness. This paper aims to analyze if the narrative can be a tool to better understand that experience, because the fact of telling one’s own story implies looking at and understanding oneself.. The article begins by linking the narrative with the first, second and third person perspectives in the context of the illness. I then analyze the relationship between narrative and illness, and how this link can favor the understanding of illness by creating a common discourse. After that, I evaluate the role played by the autobiographical story as a possibility of dialogue between author and reader. Finally, I reflect on empathy as a response to the encounter between subjectivities and its implications.